Two Cases of Extremely High-IL-6 Pan-uveitis with Subretinal Exudation and Cell Migration. (17th November 2022) - Tagami, Mizuki; Misawa, Norihiko; Sakai, Atsushi; Honda, Shigeru
ABSTRACT: Purpose: To describe two cases of extremely high-IL-6 pan-uveitis with subretinal exudation and cell migration. Methods: Pre-operative and postoperative images and IL-6 values in vitreous samples of two pan-uveitis cases were analyzed. Results: Case 1 was a 76-year-old man with blurry vision in his right eye. Fundus examination and optical coherence tomography showed vitreous opacification with vitreous cells and the presence of a white-yellowish retinal exudate with peripheral choroidal detachment all around. The IL-6 value was 16, 600 pg/ml. Case 2 was a 63-year-old man with blurry vision in his right eye. On fundus examination, there was severe vitreous opacification in his right eye. The IL-6 value was 26, 600 pg/ml. Importantly, there was good responsiveness to steroids and the TNF inhibitor. Conclusion: Unclassified intraocular inflammation might include a new category of disease with unilateral pan-uveitis with good response to steroid therapy and extremely high vitreous IL-6 values.